Central serous chorioretinopathy: risk factors for serous retinal detachment in fellow eyes - Shinojima, Ari; Mehanna, Chadi; Lavia, Carlo Alessandro; Gaudric, Alain; Tadayoni, Ramin; Bousquet, Elodie (British journal of ophthalmology, 2020)
Background/AimsTo assess risk factors for serous retinal detachment (SRD) in the fellow eye of patients with central serous chorioretinopathy (CSC) based on clinical data and multimodal imaging findings, including baseline late-phase indocyanine green angiography (ICGA).MethodsConsecutive patients with unilateral CSC were retrospectively assessed. Inclusion criteria were the availability of late-phase ICGA and a spectral-domain optical coherence tomography (OCT) macular cube for both eyes at baseline and over 3 months. Subsequent OCT of fellow eyes was reviewed to detect the development of SRD during the follow-up. Baseline medical data and multimodal imaging findings were analysed using Kaplan-Meier survival curves (log-rank test).ResultsSixty-eight patients with unilateral CSC were included. An SRD was detected in 19% of fellow eyes during a mean follow-up of 25.8±18.7 months. Hyperfluorescent plaques on midphase ICGA, hypofluorescent foci on late-phase ICGA, retinal pigment epithelium changes on fundus autofluorescence and fluorescein angiography abnormalities were associated with the occurrence of SRD (log-rank test; p<0.001, p=0.02, p=0.002 and p=0.001, respectively).ConclusionThese results suggest that the fellow eyes with specific findings on multimodal imaging in patients with unilateral CSC should be carefully followed up for possible incidence of CSC.